The Willingness of Residents to Pay for Improving Air Quality - Sana Akhtar; Aiman Riaz; Faiza Noor; Umaima Zainab; Faryal Asim (Indonesian Journal of Innovation and Applied Sciences (IJIAS), 2021)
Air pollution has become one of the major emerging issues of the 21st century. It is a serious problem for almost every developing country. Due to the rapid increase in population and industrialization, the problem of air pollution has become more serious. Various environmentalists and scientists have conducted a variety of studies and surveys to know about the current situation and further how to deal with these situations. Therefore, this paper aims to analyze the willingness of people living in the Southern region of Lahore to pay for improving the air quality. Statistical Package for Social Sciences software (version 20.0) was applied to determine the relationship between willingness to pay and powerful factors. A short time later stepwise, a linear regression model was built to determine the amount of positive Willingness to pay and to predict the mean value of Willingness to pay. The frequency and percentage of each variable were also determined through SPSS. The results revealed that out of 400 questionnaires filled by the citizens 82% of the citizens of southern Lahore showed positive response as they were in favor of Willingness to pay for improved air quality which shows their deep concern about the rising issue. And only 18% were not ready for Willingness to pay for improved air quality, the only reason for this negative response was the unawareness among the citizens. This shows that more awareness is required to create more knowledge among the citizens of Southern Lahore that bad air quality has so many depressing impacts on their health and well-being.